Postural control and knee joint importance during quiet standing in individuals with anterior cruciate ligament reconstruction - Leila Ghazaleh; Nader Farahpour; Peyman Aghaie Ataabadi; Seyyed Morteza Kazemi; Bahram Saleh-Sedghpour; Paul Allard (PLoS ONE, 2026)
There is obscurity about the role of the knee joint during quiet standing (QS) postural control. Examining the knee joint’s contribution during QS in individuals with damaged knee proprioception can help resolve the ambiguity. We investigated whether anterior cruciate ligament reconstruction (ACLR) changes the relative contribution of lower-limb joint motions and postural control during QS. This study included 12 individuals with ACLR and 12 able-bodied individuals. A motion capture system and two force plates were used. The acceleration of the joints, the acceleration of the body center of mass (COM), and the COP parameters were calculated during QS under eyes open (EO) and eyes closed (EC) conditions. In the control group under the EO condition, ankle, knee, and hip accelerations, and under the EC condition, ankle and hip accelerations were primary predictors of COM acceleration. In the ACLR group, under the EO condition, the knee and hip accelerations, and in the EC condition, the ankle, knee, and hip accelerations were prominent predictors. The ACLR group exhibited higher COP parameters than the control group in the closed-eyes condition. The knee plays a vital role in QS postural control. Improving knee proprioception modalities and lower-limb joint coordination is important in ACLR rehabilitation.